2018
DOI: 10.1002/jper.17-0588
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant health, peri‐implant mucositis, and peri‐implantitis: Case definitions and diagnostic considerations

Abstract: The objective of this review is to identify case definitions and clinical criteria of peri-implant healthy tissues, peri-implant mucositis, and peri-implantitis. The case definitions were constructed based on a review of the evidence applicable for diagnostic considerations. In summary, the diagnostic definition of peri-implant health is based on the following criteria: 1) absence of peri-implant signs of soft tissue inflammation (redness, swelling, profuse bleeding on probing), and 2) the absence of further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
210
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(231 citation statements)
references
References 55 publications
4
210
0
17
Order By: Relevance
“…These results with the conventional treatment to manage PM were markedly inferior to those reported previously in the literature ranging between 38% and 83.3% (Hallstrom, Persson, Lindgren, Olofsson, & Renvert, 2012;Heitz-Mayfield et al, 2011;Menezes, Fernandes-Costa, Silva-Neto, Calderon, & Gurgel, 2016;Pulcini et al, 2019;Riben-Grundstrom et al, 2015). However, there are other factors that influence the position of the peri-implant mucosal margin and probing depth other than the inflammatory changes, such as the implant depth; implant angulation or the thickness of the peri-implant mucosa (Renvert, Persson, Pirih, & Camargo, 2018). In fact, the GEE analysis has shown that after adjusting for baseline PPDi, differences between groups in mBI at 6-month evaluation were still statistically significant, and baseline PPDi had no impact in the results at any time point (p = 0.06).…”
Section: Discussionmentioning
confidence: 56%
“…These results with the conventional treatment to manage PM were markedly inferior to those reported previously in the literature ranging between 38% and 83.3% (Hallstrom, Persson, Lindgren, Olofsson, & Renvert, 2012;Heitz-Mayfield et al, 2011;Menezes, Fernandes-Costa, Silva-Neto, Calderon, & Gurgel, 2016;Pulcini et al, 2019;Riben-Grundstrom et al, 2015). However, there are other factors that influence the position of the peri-implant mucosal margin and probing depth other than the inflammatory changes, such as the implant depth; implant angulation or the thickness of the peri-implant mucosa (Renvert, Persson, Pirih, & Camargo, 2018). In fact, the GEE analysis has shown that after adjusting for baseline PPDi, differences between groups in mBI at 6-month evaluation were still statistically significant, and baseline PPDi had no impact in the results at any time point (p = 0.06).…”
Section: Discussionmentioning
confidence: 56%
“…The main inclusion criteria were as follows: subjects aged 21 and above, in good general health (absence of uncontrolled systemic disease and conditions), having received an implant-supported fixed dental prosthesis on an implant of length ≥8 mm, with at least one year post-loading at the time of review examination, no missing clinical or demographic data, and availability of intraoral periapical radiograph of implants taken at the following three time-points: (a) at date of fixture installation, (b) at the date of loading with the final prosthesis, and (c) at review at least one year after loading. Implants with diagnosis of peri-implantitis based on the current case definition, (Berglundh et al, 2018;Renvert, Persson, Pirih, & Camargo, 2018) were excluded. In brief, peri-implantitis was diagnosed where radiographic measurement of bone level of ≥3 mm and/or probing depth ≥6 mm was found concomitant with bleeding on probing.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…None of the included implants were diagnosed with peri-implantitis (Berglundh et al, 2018;Renvert et al, 2018), which prevents any extrapolation of findings to implants with a substantial disease. A number of case definitions for peri-implantitis are reported (Renvert et al, 2018).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing use of dental implants in oral rehabilitation, peri-implant inflammatory diseases have risen in incidence and comprise a significant clinical challenge. Peri-implant disease constitutes of peri-implant mucositis, characterized by reversible inflammation restricted to soft tissues around an implant, and, periimplantitis, characterized by peri-implant alveolar bone loss due to progression of the inflammatory lesion (Renvert et al 2018). Being multifactorial, periimplantitis is associated with a number of risk factors (Dreyer et al 2018).…”
Section: Introductionmentioning
confidence: 99%